A fault-tolerant time-triggered scheduling algorithm of mixed-criticality systems - Behera, Lalatendu (Computing, 2022)
Real-time and safety-critical systems are an integration of multiple functionalities onto a single computing platform. Some of the functionalities are safety-critical and subject to certification while the rest of the functionalities are nonsafety-critical and do not need the certification. Various researches have been done for the scheduling theory of mixed-criticality systems. But the time-triggered scheduling of mixed-criticality systems is very popular and used in industry. Since the schedule is prepared offline in a time-triggered mixed-criticality system, we need to prepare the schedule in such a way that the schedule must tolerate fault online. Hence the problem of fault-tolerance in the time-triggered system is important. This work proposes a new and novel time-triggered fault-tolerant algorithm for mixed-criticality systems. Then we show that the proposed algorithm is correct and tolerate at most one fault over the hyperperiod. Finally, we compare the proposed algorithm with the existing time-triggered scheduling algorithms for mixed-criticality systems.